Zinc Oxide Nanoparticles Interplay With Physiological and Biochemical Attributes in Terminal Heat Stress Alleviation in Mungbean (Vigna radiata L.) - Kareem, Hafiz Abdul; Saleem, Muhammad Farrukh; Saleem, Sana; Rather, Shabir A.; Wani, Shabir Hussain; Siddiqui, Manzer H.; Alamri, Saud; Kumar, Ritesh; Gaikwad, Nikhil B.; Guo, Zhipeng; Niu, Junpeng; Wang, Quanzhen (Frontiers in Plant Science, 2022)
Gradually rising atmospheric temperature is the vital component of the environment, which is anticipated as the riskiest abiotic stress for crop growth. Nanotechnology revolutionizing the agricultural sectors, notably, Zinc oxide nanoparticles (Nano-ZnO) has captured intensive research interests due to their distinctive properties and numerous applications against abiotic stresses. Mungbean (Vigna radiata L.) being a summer crop grown all over the world at an optimum temperature of 28-30°C. A rise in temperature above this range, particularly during the flowering stage, can jeopardize the potential performance of the plant. Hence, an outdoor study was performed to evaluate the effect of multiple suspensions of Nano-ZnO (0, 15, 30, 45, 60 mg L-1) on physicochemical attributes and yield of mungbean crop under heat stress. Heat stress was induced by fine-tuning of sowing time as; S1 is the optimal sowing time having day/night temperatures <40/25°C, S2, and S3 are late-sown were above >40/25°C during the flowering stage. In vitro studies on Zn release from Nano-ZnO by Inductively Coupled Plasma Mass Spectroscopy (ICPMS) disclosed that the Zn release and particles uptake from Nano-ZnO was concentration-dependent. Exogenous foliar application of Nano-ZnO significantly upstreamed the production of antioxidants and osmolytes to attenuate the shocks of heat stress in S2 and S3. Likewise, Nano-ZnO substantially rebated the production of reactive oxygen species in both S2 and S3 that was associated with curtailment in lipid peroxidation. Adding to that, foliar-applied Nano-ZnO inflates not only the chlorophyll contents and gas exchange attributes but also the seeds per pod (SPP) and pods per plant (PPP) which results in the better grain yield under heat stress. Thus, among all sowing dates, S1 statistically performed better than S2 and S3, although foliar exposure of Nano-ZnO boosted-up mungbean performance under both no heat and heat-induced environments. Hence, foliar application of Nano-ZnO can be suggested as an efficient way to protect the crop from heat stress-mediated damages with the most negligible chances of nanoparticles delivery to environmental compartments that could be possible in case of soil application.